2016
DOI: 10.5194/hess-20-859-2016
|View full text |Cite
|
Sign up to set email alerts
|

Importance of maximum snow accumulation for summer low flows in humid catchments

Abstract: Abstract. Winter snow accumulation obviously has an effect on the following catchment runoff. The question is, however, how long this effect lasts and how important it is compared to rainfall inputs. Here we investigate the relative importance of snow accumulation on one critical aspect of runoff, namely the summer low flow. This is especially relevant as the expected increase of air temperature might result in decreased snow storage. A decrease of snow will affect soil and groundwater storages during spring a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
69
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 45 publications
14
69
2
Order By: Relevance
“…We find that summer low‐flow elasticity to the annual maximum SWE ( SWE MAX ) ranges from 0.13% to 1.18% (median 0.43%), similar to values reported for the Sierra Nevada mountains and the Swiss Alps (Godsey et al, ; Jenicek et al, , ). The magnitude of low‐flow elasticity to SWE MAX depends on the correlation between low flows and SWE MAX .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…We find that summer low‐flow elasticity to the annual maximum SWE ( SWE MAX ) ranges from 0.13% to 1.18% (median 0.43%), similar to values reported for the Sierra Nevada mountains and the Swiss Alps (Godsey et al, ; Jenicek et al, , ). The magnitude of low‐flow elasticity to SWE MAX depends on the correlation between low flows and SWE MAX .…”
Section: Discussionsupporting
confidence: 88%
“…We estimated Q MIN elasticity using ordinary least squares log‐log linear regression between annual time series of Q MIN and SWE MAX , PPT , and PET (Jenicek et al, ). The method is equivalent to the bivariate parametric estimator described by Sankarasubramanian et al ().…”
Section: Methodsmentioning
confidence: 99%
“…A regional check with discharge data from catchments with similar settings shows, however, a remarkable result: The simulated annual discharge anomalies (with respect to a longer term mean) for the Dischma catchment (with time variable lapse rates) closely follow the trend of the nearby rivers (Figure ), while the observed data completely drifts away. In addition, all published simulations with similar models (with PREVAH and HBV by Orth et al, ;with HBV by Jenicek et al, ) show a comparable deviation from the observed discharge data over the period 2000–2005 (Schaefli et al, ).…”
Section: Resultsmentioning
confidence: 58%
“…Jenicek et al, 2016, and references therein), and dynamical methods, which use seasonal meteorological forecasts as input to a hydrological model. More recently, mixed approaches have been investigated to take advantage of initial land surface conditions, seasonal predictions of atmospheric variables and the predictability information contained in large-scale climate features (see Robertson et al, 2013;Yuan et al, 2015, and references therein).…”
Section: Introductionmentioning
confidence: 99%